Proposta de classificação quanto ao Dano Potencial Associado - DPA para o Estado de Roraima : estudo de caso de sete barragens situadas na bacia hidrográfica do Rio Cauamé - Pereira, Andressa dos Santos (2020)
Considering that the analysis of the potential loss of human life, as well as environmental and socioeconomic impacts that occur in the flood area, in the event of possible dam breaks, contribute to the elaboration of the Dam Safety Plan – DSP and that such analyzes are part of the objectives and instruments of the National Dam Safety Policy – NDSP, research about criteria applied to the hazard potential rating of dams that reflect in the best way the reality of the studied dams, in order to propose a rating model for the state of Roraima, based on the case study of seven dams located in the basin of the Cauamé River. Therefore, it’s necessary to analyze a rating published by resolutions CNRH n. 143/2012 and ANA n. 132/2016, when applied to the dams of the state of Roraima, to analyze in the comparative way the hazard potencial rating, using the simplified flood spot generation method and the rating made by Fundação Estadual do Meio Ambiente e Recursos Hídricos – Femarh, state supervisory sector, with its own criteria and present a proposal for the hazard potential rating of dams using complementary methodologies, associated with Normative Instruction Femarh n. 3/2017 and ANA Resolution n. 132/2016. A bibliographic and documentary research is carried out about which methodology should be used to delimit the affected area, as well as which criteria and scores are best suited to the reality of the studied dams, in order to support the proposal presented from of a qualitative approach to data. That said, the criteria established in resolutions CNRH n. 143/2012 and ANA n. 132/2016 penalized in excess the dams, because of if there is presence of human life in the affected area is attributed to a maximum score on the potential loss of life, without a quantitative distribution adequate to the reality of the state dams as to the socioeconomic impact. In addition, about the Normative Instruction Femarh n. 3/2017, check that there were some relevant divergences in the rating, because Femarh doesn’t have well-defined criteria to delimit the affected area or may have underestimated the specific area, resulting in an incompatible rating with reality. Thus, the proposal presented weighs the criteria already established at national and international level, changing ranges of ratings and inserting quantitative criteria, in order to reduce the discretion of the supervisory sector, which allows the verification that the model of proposed rating reflects the good practices used, being appropriate to the state of Roraima.